2001
DOI: 10.1073/pnas.051630498
|View full text |Cite
|
Sign up to set email alerts
|

Substratal idiothetic navigation of rats is impaired by removal or devaluation of extramaze and intramaze cues

Abstract: The spatial orientation of vertebrates is implemented by two complementary mechanisms: allothesis, processing the information about spatial relationships between the animal and perceptible landmarks, and idiothesis, processing the substratal and inertial information produced by the animal's active or passive movement through the environment. Both systems allow the animal to compute its position with respect to perceptible landmarks and to the already traversed portion of the path. In the present study, we exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…One of them may be the behavioral task used: solid ground maze employing foraging behavior in our experiments and swim-escape response in the MWM in Harker and Whishaw's (2002) studies. In addition, in a dry maze task compared to the water maze, there is a higher probability that some intramaze cues can be used together with the allothetic extramaze room cues to build a cognitive map of the environment which may differentially affect place learning in different strains (Bures, Fenton, Kaminsky, Wesierska & Zahalka, 1998;Stuchlik, Fenton & Bures, 2001). Interestingly, in both our and Harker and Whishaw's (2002) studies, regardless of the task used, the SD rats demonstrated the poorest performance in place acquisition.…”
Section: Discussionmentioning
confidence: 65%
“…One of them may be the behavioral task used: solid ground maze employing foraging behavior in our experiments and swim-escape response in the MWM in Harker and Whishaw's (2002) studies. In addition, in a dry maze task compared to the water maze, there is a higher probability that some intramaze cues can be used together with the allothetic extramaze room cues to build a cognitive map of the environment which may differentially affect place learning in different strains (Bures, Fenton, Kaminsky, Wesierska & Zahalka, 1998;Stuchlik, Fenton & Bures, 2001). Interestingly, in both our and Harker and Whishaw's (2002) studies, regardless of the task used, the SD rats demonstrated the poorest performance in place acquisition.…”
Section: Discussionmentioning
confidence: 65%
“…The appearance and texture of the arena were rotationally uniform, so it is unlikely that this rat was able to use visual or texture cues to maintain the alignment of its spatial map with the arena, but it might have been able to deposit and use local olfactory cues. In support of this possibility, there is evidence that rats can use local olfactory cues to guide navigation when visual information is absent (Lavenex and Schenk, 1998;Maaswinkel and Whishaw, 1999;Wallace et al, 2002), and rats are more impaired at navigating in the dark when local olfactory cues are shuffled than when they are stable (Stuchlik et al, 2001;Stuchlik and Bures, 2002); however, rats are more likely to use visual rather than olfactory information if both are available and the two sets of cues are in conflict (Lavenex and Schenk, 1995;Maaswinkel and Whishaw, 1999), as was the case for five of the six rats in the present study. In a follow-up experiment, the anomalous rat was found to align its spatial map with the arena in subsequent run periods when the arena had been rotated during sleep, but with the room when the arena had been rotated during active foraging.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of D1R hindered the integration of spatial cue information flow, resulting in a decrease in the number of place cells responding to changes in spatial cues in the novel environment. The representation of the environment by hippocampal place cells, however, can still be stabilized by other information flows derived from other sources, such as idiothetic cues (Gothard et al, 1996;Whishaw et al, 1997;Knierim et al, 1998;Zinyuk et al, 2000;Stuchlik et al, 2001) used in path integration (Gothard et al, 1996;Whishaw et al, 1997;McNaughton et al, 2006), with the involvement of other neurotransmitter systems such as glutamatergic systems (McHugh et al, 1996;Cho et al, 1998;Kentros et al, 1998;McHugh et al, 2007). This neural plasticity may require a longer exposure to the environment.…”
Section: Discussionmentioning
confidence: 99%